Strengthening Food Security During The Covid-19 Pandemic: Case Study In Temanggung District, Central Java Province, Indonesia. Issue 1 (August 2021) - Kurnaedi, Dede; Purnomo, Eko Priyo; Salsabila, Lubna; Setiawan, Deni; Fathani, Aqil Teguh; Agustiyara,
Abstract: The purpose of this research is to find out what policies are taken by the Temanggung Regency Government in fighting for community food security. The Covid-19 pandemic that hit Indonesia, especially Temanggung Regency, had a significant impact in increasing the unemployment rate, which was not in line with the increased nutritional needs of the community, so the government made efforts so that people could meet their regular food needs or primary needs. The method used is a qualitative research method with a descriptive approach; the data collected are primary data and secondary data obtained from the Food Security, Agriculture and Fisheries Office of Temanggung Regency through in-depth interviews conducted in March 2021. Meanwhile, secondary data were obtained from literature, media and other relevant sources. The results obtained were that the Temanggung Regency Government implemented a community empowerment policy to organize yard farming for the community at the village level targeting low-income families and farmer groups with government funding aimed at making the community at least able to meet their daily food needs. During the Covid-19 pandemic, family needs through the use of the yard or the surrounding environment without having to spend money.